Exploring the Role of Nurses in Travel Medicine to Improve Service Performance in Travelers: A Systematic Review - Komang Matalia Gandari; Luh Seri Ani; I Made Adi Wirawan (SAGE Publishing, 2024)
Nurses play an important role in travel medicine. However, information about the role of nurses in travel medicine is still limited. This systematic literature review is aimed to exploring the role of nurses in travel medicine to improve service performance in travelers. This study was systematically compiled this review based on a literature search using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method. The inclusion criteria are articles about travel health nursing, complete original articles, articles written in English and non-review articles. The quality of the studies was also assessed based on the Newcastle Ottawa Scale for observational studies. About 5 out of 257 articles were selected from 3 electronic databases, namely PubMed, Ebsco Host, and Scopus. Analysis of the 5 articles found that the role of travel health caregivers differs from country to country. The primary role of nurses in travel health in the U.S. is to conduct are-travel counseling. Nurses in the Netherlands have the authority to prescribe medicines needed for tourists. In Iris nurses play a role in providing support to the mental health of individual tourists, while in Spain, nurses play a role in emergency care for tourists. Nurses play an important role in the health of travel, including health services for travelers before and during the trip. The results of this review add to the understanding of the role of nurses in travel medicine that contributes to improving nurse performance and tourist welfare.